PELAKSANAAN PEMBELAJARAN TEKS BIOGRAFI PADA SISWA KELAS X IIS1 DI SMA SANTUN UNTAN PONTIANAK - Mulyani, Tiya; Syambasril, Syambasril; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study describes (1) the lesson plan of biography text based of SMA Santun Untan Pontianak, (2) the implementation of teaching and learning biography text of SMA Santun Untan Pontianak, (3) the result of biography text teaching and learning of SMA Santun Untan Pontianak.The method used in this study is descriptive in the form of qualitative research. The data sources of this study were the teacher of Indonesian language and tenth grade students of IIS 1, they were 31 students. The data in this study are in the form of planning, implementation, and the results of teaching learning biography text. Data collection techniques of this study were observation and documentation. Meanwhile, data collection tools are observation guidelines and recording device. Data analysis in this study includes three stages, namely: data reduction, data presentation, and data inference.The results of the study found that the lesson plan of teaching learning biography text still had weaknesses; specifically the teacher did not arrange teaching indicators lead to the demand of basic competence. The result show that students learning in average have reached the Minimum Learning Mastery Standard. Keywords: Biography Text, Teaching Learning, Tenth Students of SMA Santun Untan Pontianak